Anthropogenical influences in the underground of the Ždánice forest - Jiří Obršlík (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2004)
On the basis of the pedological research in the years 1962 and 2003 were found following results: in the underground of the Ždánice forest descended the appearance of chernozem from 64% to 39%. From the full measure. From that measure there is only 10.2% of haplic chernozem and 28.8% of eroded chernozem. Further there descended rapidly the appearence of orthic luvisol from 21.6% to just 0.6% of glyic fluvisoils from 14.4% to 9.2%. Three new soils types were registred in the year 2003: colluvial - soils 8% , antropic-soils 8.9% and pararendzin (calcavic regosol) 34.3%. On the basis of the comparison of aerial photos from the year 1971 with present state there resulted ascent of erosive damage the soil surface from 52.5% to 72.4% in the presend. Development prognosis: there will further descend the sum of haplic chernozem, will ascend the area of eroded chernozem, further will ascend the percentage of loessy regosol the ground and of antropic- soils. The greatest ascend we can await at the para - rendzins (calcavic regosols). At the majority of the soils types there will descend the quality and quantity of humus particles.